PENERAPAN MODEL INQUIRY LEARNING DALAM PEMBELAJARAN TEMATIK TERPADU DI KELAS III SEKOLAH DASAR (STUDI LITERATUR) - Yofamella, Debby; Taufik, Taufina (Universitas Negeri Padang, 2022)
The purpose of this research is to describe the application of the Inquiry Learning model in integrated thematic learning based on several previous studies, which will be observed by how much is the improvements of student learning outcomes after the learning model is applied. This research is motived by the low student learning outcomes of the students in elementary school because of many teachers that still not applied an innovative learning model and the application of integrated thematic learning characteristics that are still not visible, teachers are still using the conventional teacher-centered learning models so that students are less active in the learning process. The inquiry learning model is the learning series activities which is focused on the critical thinking and finding the answer by itself from the concerned problems. The method of this research is the study of literature or library research. By collecting 15 accredited journals that are relevant to the topic, then analyzed how great is the improvement of student learning outcomes after the Inquiry Learning method is applied. From the results of data analysis shows that the Inquiry Learning model is effective in improving student learning outcomes.